Genome-wide mapping of nuclear mitochondrial DNA sequences links DNA replication origins to chromosomal double-strand break formation in Schizosaccharomyces pombe - Lenglez, Sandrine; Hermand, Damien; Decottignies, Anabelle

(untitled) (Genome Research, 2010)
Chromosomal double-strand breaks (DSBs) threaten genome integrity and repair of these lesions is often mutagenic. How and where DSBs are formed is a major question conveniently addressed in simple model organisms like yeast. NUMTs, nuclear DNA sequences of mitochondrial origin, are present in most eukaryotic genomes and probably result from the capture of mitochondrial DNA (mtDNA) fragments into chromosomal breaks. NUMT formation is ongoing and was reported to cause de novo human genetic diseases. Study of NUMTs is likely to contribute to the understanding of naturally occurring chromosomal breaks. We show that Schizosaccharomyces pombe NUMTs are exclusively located in noncoding regions with no preference for gene promoters and, when located into promoters, do not affect gene transcription level. Strikingly, most noncoding regions comprising NUMTs are also associated with a DNA replication origin (ORI). Chromatin immunoprecipitation experiments revealed that chromosomal NUMTs are probably not acting as ORI on their own but that mtDNA insertions occurred directly next to ORIs, suggesting that these loci may be prone to DSB formation. Accordingly, induction of excessive DNA replication origin firing, a phenomenon often associated with human tumor formation, resulted in frequent nucleotide deletion events within ORI3001 subtelomeric chromosomal locus, illustrating a novel aspect of DNA replication-driven genomic instability. How mtDNA is fragmented is another important issue that we addressed by sequencing experimentally induced NUMTs. This highlighted regions of S. pombe mtDNA prone to breaking. Together with an analysis of human NUMTs, we propose that these fragile sites in mtDNA may correspond to replication pause sites.